LITERATURE REVIEW ON FLIPPED CLASSROOM METHODS IN ENGLISH LANGUAGE TEACHING - Astafi, Riki (Institut Pendidikan Tapanuli Selatan, 2025)
This literature review explores the implementation of flipped classroom methods in English language teaching (ELT), aiming to evaluate their effectiveness and challenges in enhancing language skills and learner engagement. By systematically reviewing peer-reviewed articles, conference papers, and case studies from the last decade, the research identifies common themes, benefits, and obstacles of flipped classrooms. Findings show that flipped classrooms significantly boost student engagement, motivation, and autonomous learning through interactive, student-centered environments. Teachers benefit from increased flexibility in content delivery and addressing individual student needs. However, challenges include the substantial initial time investment for preparation and the necessity of robust technological infrastructure. Additionally, some students struggle with adapting to self-directed learning. Despite these challenges, the flipped classroom method offers a promising alternative to traditional ELT approaches, with notable improvements in learner engagement and language proficiency, provided there is careful planning, adequate resources, and continuous support for both teachers and students.